An Experimental Study in Determining Basic Robotic Coding Skills of Pre-School Students with Intellectual Disabilities - Yildiz, Ezgi Pelin; Çengel, Metin (International Journal of Interactive Mobile Technologies (iJIM), 2022)
Today, it can be said that coding has become a key competence for students and people working in many different fields in the business world. It is assumed that those who seek and develop new ways to learn-teach coding will be one step ahead. The educational use of coding started with the use of the Logo programming language in the 60s.This concept has started to revive in recent years with visual programming languages such as “Alice, its code, code.org and Scratch”. These visual programming structures enable young learners to write applications without having to learn the complex code structures of traditional programming languages. In this study to develop an experimental study to determine the basic robotic coding skills of preschool students with intellectual disabilities. The sample of the study consists of a total of 20 students with studying in pre-school education institutions in a city in Türkiye. The ages of the students are between 5 years old. Semi-experimental design, one of the experimental research designs, was used in the research. In this context, 1 experimental and 1 control group was formed with the random assignment method. The materials used in both the experimental and control groups were determined as the pre-school robotic coding set U-bot starter package.5 weeks were determined as the teaching process and a total of 12 activities that served the purpose were applied to the students. During the applications, the data of the students were collected with the help of the observation form, coding skill test and after the application, they were collected through focus group interviews. As a result, at the end of the 5-week period, it was observed that there were positive significant changes in the two dependent variables (academic achievement andlearning rate) that were used as a basis for measuring the learning skills of both the experimental group and the control group students.